1994
DOI: 10.3382/ps.0730571
|View full text |Cite
|
Sign up to set email alerts
|

Supercritical Carbon Dioxide Extraction of Lipids and Cholesterol from Dehydrated Chicken Meat

Abstract: Supercritical carbon dioxide (SC-CO2) extraction was studied for removal of lipids and cholesterol from dried chicken meat powder and chunks. Two combinations of pressure and temperature were used: 299 atm and 45 C, and 381 atm and 55 C, both providing a fluid density of .90 g/cm3. For a given quantity of CO2, at the higher temperature and pressure, significantly (P < .05) more lipids and cholesterol were extracted from the powder. At 381 atm and 55 C, approximately 89% of the lipids and 90% of the cholesterol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 11 publications
2
10
0
Order By: Relevance
“…1 [20]. The SC-CO 2 extraction was operated in a single-pass mode by passing CO 2 through a fixed bed of DDGS particles, precipitating lipid extract in a separator, and finally expanding and releasing CO 2 to the ambient surroundings.…”
Section: Sc-co 2 Extractionmentioning
confidence: 99%
“…1 [20]. The SC-CO 2 extraction was operated in a single-pass mode by passing CO 2 through a fixed bed of DDGS particles, precipitating lipid extract in a separator, and finally expanding and releasing CO 2 to the ambient surroundings.…”
Section: Sc-co 2 Extractionmentioning
confidence: 99%
“…The extraction of specific lipid components, such as cholesterol, can be accomplished with SC-CO2 as reported in the literature (Ong et al 1990;Froning et al 1994;Boselli et al 1997). The problem from an analytical perspective are the large number of co-extractives that also exhibit sufficient solubilities in SC-CO2 which are co-extracted along with the desired solute (analyte).…”
Section: Application Of Analytical Sfe To Fats Oils and Lipidsmentioning
confidence: 99%
“…At this regard, benign supercritical CO 2 extraction seems promising as it possesses many desirable features for separating and purifying desired components from natural products and foods. Therefore, a number of recent studies have been contributed to the cholesterol reduction by using supercritical fluid extraction methodology from cattle brain (Vedaraman et al, 2004(Vedaraman et al, , 2008, cow brain (Vedaraman et al, 2005), shrimp (Higuera-Ciapara et al, 2005), pork (Lin et al, 1999), chicken meat (Froning et al, 1994), turtle fish egg (Shen et al, 2008), egg yolk (Bringe, 1997;Froning et al, 1998), butter oil (Mohamed et al, 1998(Mohamed et al, , 2000 and squid oil (Kang et al, 2005). These researches have indicated that supercritical fluid extraction technology holds promise for substantially reducing cholesterol contents and thus offers an alternative to current methods of developing low-cholesterol foods.…”
Section: Introductionmentioning
confidence: 97%